2014
DOI: 10.3171/2014.2.peds13528
|View full text |Cite
|
Sign up to set email alerts
|

Filum terminale lipomas: imaging prevalence, natural history, and conus position

Abstract: Object Filum terminale lipomas (FTLs) are being identified with increasing frequency due to the increasing utilization of MRI. Although an FTL may be associated with tethered cord syndrome (TCS), in many cases FTLs are diagnosed incidentally in patients without any symptoms of TCS. The natural history of FTLs is not well defined. Methods The authors searched the clinical and imaging records at a single i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 35 publications
0
40
0
9
Order By: Relevance
“…Although this quality improvement initiative did not compare strategies regarding the length of time that patients were kept flat, our finding of a 3.8% (6/160) postoperative CSF leak rate was between the 5.9% rate reported by Chern and colleagues 1 and the 1.9% (1/52) and 0% rates reported by Cools and colleagues 3 and Ogiwara and colleagues, respectively. 7 Both Chern and Ogiwara found that Post = postintervention; Pre = preintervention.…”
Section: Discussionmentioning
confidence: 35%
See 1 more Smart Citation
“…Although this quality improvement initiative did not compare strategies regarding the length of time that patients were kept flat, our finding of a 3.8% (6/160) postoperative CSF leak rate was between the 5.9% rate reported by Chern and colleagues 1 and the 1.9% (1/52) and 0% rates reported by Cools and colleagues 3 and Ogiwara and colleagues, respectively. 7 Both Chern and Ogiwara found that Post = postintervention; Pre = preintervention.…”
Section: Discussionmentioning
confidence: 35%
“…Although many reports detail neurological and urological outcomes following surgical intervention for OSD, [3][4][5][6]9 there is less discussion in the literature regarding perioperative management protocols for variants of OSD that are not associated with substantial tissue defects. 1,7 Because many patients have minimal or no symptoms at the time of operative detethering, the importance of complication avoidance in this population is paramount.…”
mentioning
confidence: 99%
“…These are easily distinguished from more rare DSTs, occurring in approximately 1 in 1500‐2500 live births . Cadaveric studies demonstrate a 4‐6% prevalence of filum terminale lipomas, whereas MRI suggests a prevalence of 0.24‐4% . Spinal cord lipomas are detected in 3‐8/100 000 births .…”
Section: Introductionmentioning
confidence: 99%
“…A conus position below the inferior margin of the L-2 body is generally considered low-lying at our institution. 6 Patients with syringes that were secondary to spinal tumor, spinal trauma, and other conditions such as infection and spinal arachnoid cyst were also considered separately. Patients were excluded if there was a history of CM Type II or open spinal dysraphism.…”
Section: Following University Of Michigan Institutional Reviewmentioning
confidence: 99%